Does Human Rights Disclosure Enhance Firm Value? - Elisa Tjondro; Clarissa Wijoyo; Livia Mei Indah; Yessica Chandra; Tonny Stephanus Eoh (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2022)
The objective of this research is to explain the effect of human rights disclosure, independent commissioners, and family ownership on firm value. We also analyzed descriptively human rights disclosures for three periods, which is from 2017-2019, in Indonesia. UNGP-BHR and the Indonesian State Law No. 39 of 1999 about Human Rights are used as the disclosure index checklist. This study uses 345 non-financial companies that are fully listed for three periods on the Indonesia Stock Exchange (IDX). The data used were collected from Bloomberg and Annual Report, which had been taken from the official website of IDX and the official website of the sample companies. The data analysis technique used to test our hypothesis is panel regression. The main result of this study showed that human rights disclosure and independent commissioners have a positive impact on firm value, while family ownership negatively affects firm value. We also found that each item of human rights disclosure increased during the observation period, in which the least disclosed item was related to engagement with external human rights experts to undertake human rights issues. The implication of this research is that increasing human rights disclosure provides a positive image for the investors and creditors.